Filter Aided Sample Preparation – A tutorial - Wiśniewski, Jacek R. (Analytica chimica acta, 2019)
Filter Aided Sample Preparation (FASP) is a widely used protein processing technique in “bottom-up” proteomics. Its popularity reflects the key features of the method: its applicability to a variety of sample types and the high quality of the released peptides. Successful application of FASP requires optimized properties of sample lysate and its amount, use of ultrafiltration units with membranes having large molecular mass cut-offs and well selected conditions for protein digestion. In contrast to the majority of sample preparation methods, FASP allows digestion of proteins with a variety of enzymes and a straightforward monitoring of protein-to-peptide conversion. A unique feature of FASP is the possibility to cleave proteins in a consecutive way using several proteases and to separate peptide fractions. Understanding principles of the method gives guidance in applying FASP to different types of samples in optimization of conditions of the FASP-workflow. [Display omitted] •Filter Aided Sample Preparation method allows efficient sample preparation for “bottom up” LC-MS proteomic analysis.•Molecular foundations of the method are described.•Technological constrains of FASP are discussed.•This is a guide to the FASP method providing hints for optimization of sample preparation workflows.